Pengaruh Latihan Variasi Terhadap Keterampilan Passing Bawah Siswa Esktrakurikuler Bola Voli Di SMP Negeri 5 Kabupaten Seluma - Saputra, Septian Aji; Sumantri, Ajis; Perdima, Feby Elra (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to determine the extent of the effect of variation training on improving underhand passing skills among volleyball extracurricular students at SMPN 5 Seluma. This research is an experimental study, using a pre-experimental design, which is a development method of the one-group pretest-posttest design. The population in this study consisted of 22 students from SMPN 5 Seluma Regency. This can be seen from the average improvement in underhand passing skills over ten training sessions, measured through pre-test and post-test data. The pre-test results showed the highest score of 13, the lowest score of 7, and an average of 9.81. The post-test results showed the highest score of 18, the lowest score of 12, and an average of 14.95. The initial test average of 9.81 increased to 14.95 in the final test. The t-test results indicate a significant difference between the pre-test and post-test scores, where the tvalue (28.90) is greater than the ttable value (2.195), confirming that the research hypothesis is accepted. This is further supported by a correlation value of 0.729, indicating a fairly strong and positive relationship between pre-test and post-test results. It can be concluded that the variation training method positively contributes to improving underhand passing skills in volleyball among students at SMPN 5 Seluma Regency.